Penerapan Uji Fungsionalitas dan Uji Pengguna Augmented Reality Word Warrior Sebagai Media Ajar Kosakata Bahasa Inggris - Andam Lukcyhasnita; Ferry Fachrizal; Juneidy (Bulletin of Computer Science Research, 2024)
This research developed and tested the "Word Warrior" game based on Augmented Reality (AR), applied as an Instagram filter, as a medium for teaching English vocabulary. The method used was Research and Development (R&D) with the 4D model (Define, Design, Development, Dissemination). The study focused on functionality and user testing. Functionality testing showed that all game features worked according to specifications after several improvements. User testing involved students from Politeknik Negeri Medan, indicating that the game is easy to use and well-received, with an overall product rating of 78.5. The lowest average score was found in the game mechanics aspect, with a value of 77.5, although this aspect was still rated as good. This will serve as a basis for future evaluations and improvements to enhance the comfort and ease of use for future players. In conclusion, the AR-based "Word Warrior" game effectively serves as a vocabulary teaching medium, meeting user needs and expectations, and providing important references for the further development of AR-based educational games in the future.